INTELLIGENCE AND ACADEMIC ACHIEVEMENT AS PREDICTORS OF READING DISABILITY: A COMPARATIVE STUDY - Mufti, Sarah; Akram, Bushra; Ahmad, Fayyaz (Journal of Peace, Development and Communication, 2021)
Children at risk of dyslexia face problems in academic achievement and they were often viewed as children with low intelligence. The purpose of the study was to investigate the relationship between academic achievement and intelligence. The study also aimed to find out academic achievement and intelligence as predictors of children at risk of dyslexia. The study was conducted from September 2020 to November 2020. Sample of 268 students exhibiting problems in reading, writing or mathematical expression was selected from 1532 students with the help of teachers. Dyslexia screening test Junior (DST-J) was used for screening (Nicolson & Fawcett, 1996). Standard Progressive Matrices (SPM) (Raven, Raven, & Court, 1998) were used to assess intelligence. Academic record of all the students was obtained based on their performance in last examination. Results showed children had above average intelligence. Further, academic achievement showed significant positive relationship with intelligence (r=.32, p<.001). Moreover, intelligence and academic achievement were found to be significant predictors of performance of children at risk of dyslexia. Results concluded that children should be given intervention to improve their academic performance.